Crop diversity, climate change adaptation and resilience: good practice cases from Africa - Vernooy, Ronnie; Adokorach, Joyce; Coulibaly, Harouna; Fadda, Carlo; Jeko, Manata; Kakeeto, Ronald; Kasasa, Patrick; Sikitu Kazungu, Jonathan; Mapanda, Sipiwe; Mollel, Margaret; Wasswa Mulumba, John; Mushita, Andrew; et al. (2021)
As part of the Integrated Seed Sector Development in Africa (ISSD Africa) program’s activities for 2020, the Agrobiodiversity, seeds and climate change action learning group (Theme 3) documented and analyzed a series of good crop diversification practice cases from Africa, which were published in an ISSD Africa working paper [https:// hdl.handle.net/10568/115012]. This brief presents a synthesis of the working paper.